Chapter 10 Balance on Every Ledger Kwakwaka'wakw resource values and traditional ecological management - Deur, Douglas (Taylor & Francis, 2021)
This chapter illustrates the core environmental values of the Kwakwaka'wakw (Kwakiutl) people on the Pacific coast of Canada to explore how they manifest in the traditional management of coastal natural resources. The authors' survey of environmental values is based on the authentic knowledge of Chief Adam Dick, a co-author of the chapter. The chapter argues that talking about Indigenous Knowledge without the broader context of environmental values can lead to serious scholarly misunderstandings and insists that long-term collaborations between academic researchers and specialized knowledge holders from Indigenous communities is necessary in order to represent Indigenous Knowledge accurately.